Effect of Transformational Leadership and Work Stress on Organizational Citizenship Behavior with Organizational Commitment as an Intervening Variable - Arrozi, Muhammad Fachruddin; Tirtayasa, Charli Otman; Nofiarni, Nofiarni (Alta Dharma Publisher, 2022)
Background. Organizational citizenship behavior (OCB) is defined as behavior that goes beyond formally defined roles and is not stated in the job description. Objective: The study aimed to examine the effect of Organizational Citizenship Behavior (OCB) that are influenced by the Transformational Leadership of the Head of the Inpatient Room, work stress, and nurse organizational commitment simultaneously. Method: This research uses a survey method with an explanatory causality approach. Data was collected by using a questionnaire and tested using Multiple Linear Regression Analysis. Result: Transformational leadership, job stress, and organizational commitment significantly affect organizational citizenship behavior simultaneously. Transformational leadership is the biggest factor. Organizational commitment can mediate the effect of Transformational Leadership and work stress on Organizational Citizenship Behavior. Transformational leadership significantly affects Organizational Commitment, Work Stress significantly affects Organizational Commitment, Organizational Commitment significantly affects Organizational Citizenship Behavior, and Transformational Leadership significantly affects Organizational Citizenship Behavior. Work stress significantly affects Organizational Citizenship Behavior. Implication: This study helps hospital management to promote a more effective work culture through Transformational Leadership training, Organizational Citizenship Behavior of Heads of Inpatient rooms, and a new method of selecting new nurses recruitment by HRD and long-term prosocial improvement for senior employees